The McElderry book of Mother Goose - Mathers, Petra (Margaret K. McElderry Books, 2012)
An illustrated collection of Mother Goose nursery rhymes, including well-known ones such as "Hey Diddle Diddle" and "The Queen of Hearts" and less familiar ones such as "Mother May I Go and Swim" and "Ten Little Penguins."